2020
DOI: 10.14202/vetworld.2020.1697-1708
|View full text |Cite
|
Sign up to set email alerts
|

Unique patterns of cardiogenic and fibrotic gene expression in rat cardiac fibroblasts

Abstract: Background and Aim: Cardiac fibroblasts are important for both normal and pathological states of the heart, but the knowledge in cell physiology and genomics is still poorly understood. The aims of the present study were; first, to investigate the expression of cardiac and fibrotic genes in rat cardiac fibroblasts compared to cardiomyocytes and other fibroblasts (skin and muscle fibroblasts), second, to examine the in vitro effect of serum concentration on fibroblast gene expression. The findings can potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Of note, the data described so far are in contrast with those reported by Perez-Aso et al using a murine model of fibrosis, which demonstrated that the increase in BGN expression was not prevented by ZM241385 administration [ 47 ]. These two conflicting results might be explained by the use of different experimental models; cardiac fibroblasts have a distinct pattern of gene expression compared to other fibroblasts, such as those observed in the skin [ 48 ]. Furthermore, skin fibrosis was induced via mechanical injury, and therefore, our different results could also be due to other pathways activated by TGF-β under different experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the data described so far are in contrast with those reported by Perez-Aso et al using a murine model of fibrosis, which demonstrated that the increase in BGN expression was not prevented by ZM241385 administration [ 47 ]. These two conflicting results might be explained by the use of different experimental models; cardiac fibroblasts have a distinct pattern of gene expression compared to other fibroblasts, such as those observed in the skin [ 48 ]. Furthermore, skin fibrosis was induced via mechanical injury, and therefore, our different results could also be due to other pathways activated by TGF-β under different experimental conditions.…”
Section: Discussionmentioning
confidence: 99%